Clozapine Induced Pericarditis: A Systematic Review - Aliu Yakubu; Olorungbami Anifalaje; Moses Effiong; Oluwakemi Olalude; Maryam Abubakar (BJPsych Open, 2025)
Aims: Clozapine is an atypical antipsychotic for treatment-resistant schizophrenia. Despite its efficacy, there are potential life-threatening side effects, including pericarditis, which has limited its usage. Clozapine-induced pericarditis may range from mild symptoms to life-threatening complications. Despite increasing case reports, a comprehensive synthesis is lacking, necessitating a systematic review.